LONGITUDINAL OPTICAL DENSITY ANALYSIS OF SUBRETINAL FLUID AFTER SURGICAL REPAIR OF RHEGMATOGENOUS RETINAL DETACHMENT. Issue 1 (January 2015) - Kashani, Amir H.; Cheung, Albert Y.; Robinson, Joshua; Williams, George A.
Abstract : Purpose: To investigate optical coherence tomography–derived reflectivity and optical density (OD) characteristics of persistent subretinal fluid (SRF) in eyes after surgical repair of macula-off rhegmatogenous retinal detachment. Methods: Retrospective case series of nine eyes with macula-off rhegmatogenous retinal detachment that underwent surgical repair with either scleral buckling or vitrectomy with or without scleral buckling. Major inclusion criteria included 1) availability of high-quality optical coherence tomography scans at 2 or more time points, and 2) sufficient SRF for optical coherence tomography sampling without including tissue edges. Demographic, clinical, and optical coherence tomography imaging data were collected on all eyes. Optical density and SRF height measurements were obtained using a manual image segmentation method with ImageJ. Optical density measurements were standardized by conversion to optical density ratios to facilitate comparison between different visits and eyes. Correlations were assessed for significance through both univariate and multivariate regression analyses. Results: Optical density ratio measurements increased with time after surgery, and this was statistically significant ( P = 0.001, R 2 = 0.331). Subretinal fluid height measurements decreased in all eyes. There was a significant correlation between optical density ratios and log of SRF height ( P ⩽ 0.001, R 2 = 0.485). In multivariate analysis, neither optical density ratios nor SRF height was a statistically significant predictor of visual acuity. Conclusion: Changes in optical density ratios of the residual SRF after retinal detachment repair may be representative of changes in the SRF composition over time. This is in agreement with previous biochemical studies and may serve as a noninvasive method of assessing SRF content in vivo. Abstract : The optical coherence tomography–derived reflectivity and optical density characteristics of persistent subretinal fluid were investigated in eyes after surgical repair of macula-off rhegmatogenous retinal detachment. Changes in residual subretinal fluid reflectivity and optical density ratios after retinal detachment repair may be representative of changes in the composition of the subretinal fluid over time.